Sliding-Mode Observer-Based Mechanical Parameter Estimation for Permanent Magnet Synchronous Motor - Zhang, Xiaoguang; Li, Zhengxi (IEEE transactions on power electronics, 2016)
A mechanical parameter estimation algorithm for permanent magnet synchronous motor (PMSM) drive systems based on sliding-mode observer is proposed in this paper. First, an extended sliding-mode mechanical parameter observer (ESMMPO) is presented to track system disturbances in real time, which include the information of mechanical parameters. Based on this ESMMPO, the mechanical parameter can be extracted from the estimated system disturbance. Therefore, a simple algorithm for mechanical parameter estimation of the PMSM control system is presented. The parameter choice guidelines of ESMMPO are designed to guarantee the global stability of the observer. Then, the equivalent low-pass filter function of the ESMMPO is presented to suppress the sliding-mode chattering, which allows softening the output signal of observer while maintaining no phase lag incurring. Therefore, the smooth output of the ESMMPO can be directly used for the parameter estimation. Experimental results show the validity of the proposed parameter estimation approach.